2014
DOI: 10.4103/1319-3767.126322
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasminogen activator inhibitor-1 gene polymorphism with inflammatory bowel disease in Iranian Azeri Turkish patients

Abstract: Background/Aim:Previous studies have shown the association of some genetic factors, such as Plasminogen activator inhibitor type-1 (PAI-1) 4G/5G polymorphism, with the development of inflammatory bowel disease (IBD). We aimed to study this polymorphism as a risk factor in IBD patients in this cohort.Patients and Methods:One hundred and fifteen IBD patients and 95 healthy controls were selected from Iranian Azeri Turks and -6754G/5G polymorphism of PAI-1 gene was tested by polymerase chain reaction using allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Tissue plasminogen activator and urokinase are both associated with inflammation and the process of wound healing [ 124 ]. SERPINE1 and proteins in the downstream of its specific pathway have also been reported to be directly associated with IBD as a functional regulator [ 125 , 126 ]. As a candidate gene, we also predicted an angiogenesis-associated gene VEGFC , which regulates angiogenesis and endothelial cell growth [ 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tissue plasminogen activator and urokinase are both associated with inflammation and the process of wound healing [ 124 ]. SERPINE1 and proteins in the downstream of its specific pathway have also been reported to be directly associated with IBD as a functional regulator [ 125 , 126 ]. As a candidate gene, we also predicted an angiogenesis-associated gene VEGFC , which regulates angiogenesis and endothelial cell growth [ 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…30 Therefore, seems that the lack of JAK2 V617F mutation in our study was due to the small samples of patients with IBD having thromboembolism, who none of them had MPN complication, or this mutation in patients with IBD is low. Also, several studies have shown the role of other factors in the pathogenesis of IBD's thrombosis such as fibrinolysis system, 10,31-33 plasma coagulation inhibitors, 31,34,35 homocysteine, 31,36,37 platelet disorders, 31,38,39 autoantibodies, 9,40 and genetic factors [such as Factor Ⅴ Leiden G1691A mutation, 41 pro-thrombin G20210A muta-tion, 42 methylene-tetra-hydrofolate reductase C677T mutation, 43 and plasminogen activator inhibitor type 1 (PAI-1) mutation 44 .…”
Section: Discussionmentioning
confidence: 99%